Population dynamics of ticks on indigenous cattle in a pastoral dry to semi-arid rangeland zone of Uganda - Okello-Onen, Joseph; Tukahirwa, E.M.; Perry, Brian D.; Rowlands, G.J.; Nagda, S.M.; Musisi, G.; Bode, E.; Heironen, R.; Mwaji, W.; Opuda-Asibo, J. (Springer, 1999)
Studies on seasonality and population dynamics of ticks on indigenous cattle and their crosses (calves) were carried out in Buruli Ranching Scheme, Nabiswera, Luwero District of Uganda on three treatment groups of animals: group 1 (twice a week dipping), group 2 (once a month dipping) and group 3 (no tick control). During this study, four major species of ticks of economic importance were recorded in decreasing order of abundance: Rhipicephalus appendiculatus. Rhipicephalus evertsi evertsi, Amblyomma variegatum and Boophilus decoloratus. Of these ticks, a seasonal pattern of activity was only observed in R. appendiculatus ticks, with peak activities occurring during rainy seasons. Greater numbers of ticks were recorded on cows than calves in the three treatment groups, with the exception of A. variegatum where the reverse occurred. The mean numbers of ticks per animal were highly significantly different (p<0.01) when group 1 animals were compared with group 2 and 3 animals. However, no significant differences (p>0.05) were observed in mean tick numbers between group 2 and 3 animals. Highly sigificant differences (p<0.01) were observed in mean tick numbers on cows and calves (more than 12 months old) in different calving seasons. The state of lactation only affected tick counts on cows in group 1; significantly more ticks (p<0.01) were observed in lactating than non-lactating cows. Furthermore, significantly greater (p<0.05) numbers of ticks (with the exception of B. decoloratus) were recorded during the second year of study (March 1992-May 1993) than the first year (January 1991-Feburary 1992), despite lower rainfall during the former period.